Representasi Heroisme Sosok Ayah dalam Film Maharaja: Analisis Semiotika Roland Barthes atas Makna Perlindungan - Rendy Setya Nugroho; Didi Permadi; Ike Desi Florina (Universitas Medan Area, 2026)
This study aims to analyze the representation of fatherly heroism in the film Maharaja using Roland Barthes’ semiotic approach. This research applies a descriptive qualitative method, with selected scenes depicting Maharaja’s relationship with his child as the object of analysis. Primary data were obtained through observation and documentation of scenes, dialogues, expressions, gestures, settings, and visual symbols in the film, while secondary data were collected from literature related to representation, heroism, fatherhood, film, and semiotics. The analysis was conducted through Barthes’ three levels of meaning: denotation, connotation, and myth. The findings show that fatherly heroism in Maharaja is represented through affection, protection, emotional presence, responsibility, defense of the child’s dignity, and the pursuit of justice. At the mythical level, the father is constructed as a family hero with a moral obligation to protect his child. However, this representation remains ambiguous because it intersects with violence, revenge, and protective masculinity.